2018
DOI: 10.24071/llt.2018.suppl2110
|View full text |Cite
|
Sign up to set email alerts
|

Paired Oral Tests: A Literature Review

Abstract: This paper reviews the studies on paired oral tests in the last ten years (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017). Using the search facilities in Iowa State University's library, nine articles from some journals in the field of applied linguistics were chosen based on the inclusion criteria. Those journals are Language Testing, Language Assessment Quarterly, Applied Linguistics, and Procedia -Social and Behavioral Science. Three reasons why paired oral tests are better than interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…As has been noted by Malone and Montee (2010), though OPIs are implemented by trained and certified testers, "…human error is inevitable and can be limited but not eliminated" (p. 978). In this regard, pairing or even grouping the test-takers and asking them to interact with each other may help remedy this weakness (Brooks, 2009;Brown & Abeywickrama, 2018;Green, 2021;Hırçın Çoban, 2017;Jankowska & Zielińska, 2015;Louma, 2004;Prasetyo, 2018;Sandlund et al, 2016) because, as has been reported by Ahmadi and Sadeghi (2016) and Brooks (2009), positive washback, more natural discourse and more various language functions can be attained and the workload of the rater in terms of time, effort and cost may be reduced. Moreover, when test-takers are paired or grouped, they tend to feel less anxious in comparison to the traditional OPI (Hırçın Çoban, 2017).…”
Section: Pros and Cons Of The Opimentioning
confidence: 99%
“…As has been noted by Malone and Montee (2010), though OPIs are implemented by trained and certified testers, "…human error is inevitable and can be limited but not eliminated" (p. 978). In this regard, pairing or even grouping the test-takers and asking them to interact with each other may help remedy this weakness (Brooks, 2009;Brown & Abeywickrama, 2018;Green, 2021;Hırçın Çoban, 2017;Jankowska & Zielińska, 2015;Louma, 2004;Prasetyo, 2018;Sandlund et al, 2016) because, as has been reported by Ahmadi and Sadeghi (2016) and Brooks (2009), positive washback, more natural discourse and more various language functions can be attained and the workload of the rater in terms of time, effort and cost may be reduced. Moreover, when test-takers are paired or grouped, they tend to feel less anxious in comparison to the traditional OPI (Hırçın Çoban, 2017).…”
Section: Pros and Cons Of The Opimentioning
confidence: 99%